THE INFLUENCE OF INSTRUCTIONAL LEADERSHIP ON TEACHERS DISCIPLINE AND PRODUCTIVITY IN POLICE LANGUAGE SCHOOL - Siti Roniyah; Heru Santosa; Francis Tantri (Peneliti.net, 2019)
This study aims to determine the effect of principals 'instructional leadership on the productivity of educators, the influence of discipline on the productivity of educators, and the influence of principals' instructional leadership on the discipline of educators. This research is a quantitative study with a survey method. Data analysis using path analysis. The population and sample in this study were all teaching staff in the Police Language School. Data was obtained by giving questionnaires on instructional leadership, discipline, and productivity to 50 educators in the Police Language School. From the processed data obtained three results of research, namely: there is a positive direct influence between principals 'instructional leadership on the productivity of educators, there is a positive direct influence between discipline on the productivity of educators, and the final results there is a positive direct influence of principals' instructional leadership on teacher discipline.